2021
DOI: 10.1089/thy.2020.0322
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Lenvatinib and Pembrolizumab Is an Effective Treatment Option for Anaplastic and Poorly Differentiated Thyroid Carcinoma

Abstract: Background: Anaplastic thyroid carcinoma (ATC) and metastatic poorly differentiated thyroid carcinomas (PDTCs) are rare aggressive malignancies with poor overall survival (OS) despite extensive multimodal therapy. These tumors are highly proliferative, with frequently increased tumor mutational burden (TMB) compared with differentiated thyroid carcinomas, and elevated programmed death ligand 1 (PD-L1) levels. These tumor properties implicate responsiveness to antiangiogenic and antiproliferative multikinase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(112 citation statements)
references
References 51 publications
2
104
0
6
Order By: Relevance
“…In a recent series of metastatic ATC and PDTC negative for the BRAF V600E mutation, 8 patients received a combination therapy of LEN and PEM for a maximum of 40 months after failing chemotherapy, radiation or radioiodine therapy. The combination treatment was not only well tolerated with 50% (3/6) of ATC patients still on therapy at data cutoff but also led to complete response (CR) in 66% (4/6) of ATC patients after 7, 10 and 12 months and PR in 75% of patients after three to four months of treatment ( 28 ). Range of PD-L1 expression was 1%-90% and patients with a PD-L1 expression greater than 50% (5/8) responded best to combination therapy ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent series of metastatic ATC and PDTC negative for the BRAF V600E mutation, 8 patients received a combination therapy of LEN and PEM for a maximum of 40 months after failing chemotherapy, radiation or radioiodine therapy. The combination treatment was not only well tolerated with 50% (3/6) of ATC patients still on therapy at data cutoff but also led to complete response (CR) in 66% (4/6) of ATC patients after 7, 10 and 12 months and PR in 75% of patients after three to four months of treatment ( 28 ). Range of PD-L1 expression was 1%-90% and patients with a PD-L1 expression greater than 50% (5/8) responded best to combination therapy ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…The combination treatment was not only well tolerated with 50% (3/6) of ATC patients still on therapy at data cutoff but also led to complete response (CR) in 66% (4/6) of ATC patients after 7, 10 and 12 months and PR in 75% of patients after three to four months of treatment ( 28 ). Range of PD-L1 expression was 1%-90% and patients with a PD-L1 expression greater than 50% (5/8) responded best to combination therapy ( 28 ). There was no association of PD-1 expression or frequency of tumor infiltrating lymphocytes (TILs) with treatment response ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this series, fatigue, anemia and hypertension were the most common AEs associated with this combination and drug-induced rash and altered mental status (likely related to PD) induced drug interruption [152]. Similarly, Dierks et al showed interesting results about lenvatinib and pembrolizumab combined treatment both in ATC and PDTC: 5/6 patients with ATC reached CR/PR and 2/2 with PDTC obtained PR [153]. Similarly, nivolumab (anti-PD1 antibody) was added to vemurafenib in patients affected by metastatic ATC, obtaining a prolonged response (more than 20 months) [154].…”
Section: Multimodal Therapymentioning
confidence: 55%
“…In addition, multiple clinical trials with VEGF and/or VEGF inhibitor and immune checkpoint inhibitors have been designed. Pemproblizumab plus lenvatinib was investigated in a phase 2 trial for unresectable ATC (NCT04171622) as well as in a randomized study in a small group of advanced ATC and PDTC [162]. The same combination is under study in DTC and PDTC naïve or progressing after lenvatinib patients (NCT02973997).…”
Section: Immunotherapymentioning
confidence: 99%